Communications, Signal Processing, and Systems Proceedings of the 2017 International Conference on Communications, Signal Processing, and Systems - Liang, Qilian; Mu, Jiasong; Jia, Min.; Wang, Wei.; Feng, Xuhong; Zhang, Baoju; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together papers presented at the 2017 International Conference on Communications, Signal Processing, and Systems (ICCSP 2017), which was held on July 14-17, 2017 in Harbin, China. Presenting the latest developments and discussing the interactions and links between these multidisciplinary fields, the book spans topics ranging from communications, signal processing and systems. It is aimed at undergraduate and graduate electrical engineering, computer science and mathematics students, researchers and engineers from academia and industry as well as government employees.
Wireless communications -- Wireless networks -- Internet of Things -- Wireless sensor networks -- Signal processing for communications and networking -- Audio and acoustic signal processing -- Bio imaging and signal processing -- Machine learning for signal processing -- Sensor array and multichannel signal processing -- Design and implementation of signal processing systems -- Circuits and Systems for Communications -- Neural Networks and Systems -- Fuzzy Logic Systems -- Nonlinear Systems for Communications and Signal Processing.
Keywords: Telecommunication; Electronic circuits; Signal processing; Communications Engineering, Networks; Electronic Circuits and Systems; Signal, Speech and Image Processing